Systemic administration with tetrahydrocannabinol causes retinal damage in BALB/c mice. (March 2020) - Zhang, Z; Li, R; Lu, H; Zhang, X
Recent years have seen substantial shifts in cultural attitudes towards cannabis for medical and recreational use. However, legalizing recreational marijuana may have adverse effects on individual and public health. As the most widely used illicit agent, cannabis is commonly reported to disrupt learning and memory. Unfortunately, the molecular mechanisms underlying behavioral impairment by cannabis abuse remain poorly understood. Tetrahydrocannabinol (THC), a major component in cannabis, causes short-term effects on the visual system, but little is known about persisting visual disturbances. This study was to investigate the effects of systemic administration with THC on retina and explore its underlying mechanisms. BALB/c mice were treated with 1 or 2 mg/kg THC intraperitoneally daily for 2 months, mice treated with vehicle as negative control. The retinal function was tested by electroretinography after THC treatment. Morphology and pathology changes of retina were detected by hematoxylin and eosin staining. Terminal deoxynucleotidyl transferase dUTP nick end labeling assay was used to detect the apoptosis in photoreceptor cells. Enzyme-linked immunosorbent assay was used to show the inflammatory responses and oxidative stress. mRNA and protein changes were measured by real-time polymerase chain reaction and Western blot to explore the underlying mechanisms. Results indicated that 2-month treatment with THC caused retinal damage, evidenced by its functional loss and increased apoptosis in photoreceptor cells through inducing inflammatory responses and oxidative stress. Our study demonstrated that systemic administration with THC caused toxic effects on retinas of BALB/c mice, suggesting the potential mechanisms for the retina damage caused by cannabis abuse.